Inflammation markers in virologically suppressed HIV-Infected patients after switching to dolutegravir plus lamivudine vs continuing triple therapy: 48-week results in real-life setting. Issue 1 (31st December 2022) - Lombardi, Francesca; Belmonti, Simone; Moschese, Davide; Fabbiani, Massimiliano; Borghetti, Alberto; Ciccullo, Arturo; Visconti, Elena; Di Giambenedetto, Simona
Abstract : Objectives: To evaluate the impact of a treatment switch to dolutegravir plus lamivudine on the soluble inflammatory biomarkers of HIV-infected patients treated in a real-life setting. Materials and methods: This was a longitudinal study that enrolled virologically-suppressed patients on stable 3-drug ART who switched at baseline to dolutegravir + lamivudine (2DR-group), based on the clinician's decision, or maintained triple therapy (3DR-group). Subjects in the 3DR-group were matched with those in the 2DR-group for age, gender and type of anchor drug. Plasma levels of interleukin-6 (IL-6), I-FABP, D-dimer and C-reactive protein (CRP) were quantified by a microfluidic ultrasensitive ELISA assay at baseline and at 48 weeks. Results: Overall 208 subjects were enrolled: 101 in the 2DR-group and 107 in the 3DR-group. At baseline, biomarker levels were comparable between groups. The differences in mean log10 change from baseline to 48 weeks between groups (2DR versus 3DR) were: IL-6 (pg/L) −0.051(95% CI −0.115/0.009) versus 0.004 (95% CI −0.046/0.054) (p = 0.159); I-FABP (pg/mL), −0.088 (95% CI −0.14/-0.041) versus 0.033 (95%CI −0.007/0.072) (p < 0.001); D-dimer (pg/mL), −0.011(95% CI-0.055/0.033) versus −0.021 (95% CI −0.071/0.030) (p = 0.780) and CRP (pg/mL), −0.028 (95%CI −0.118/0.063) versus 0.118 (95% CI 0.024/0.211) (p = 0.028). Conclusions: At 1 year, switching to a dolutegravir plus lamivudine dual regimen in this setting showed a favorable trend for two biomarkers analyzed, i.e., I-FABP and CRP, as compared to continuing a triple therapy. These results add important new data in support of the safety of this approach in terms of its effect on the inflammatory milieu.